Effect of NPK Fertilizers on Seedling Growth of Mangrove Species - Miah, Md. Abdul Quddus; Moula, Md. Golam (International Journal For Research In Agricultural And Food Science, 2019)
An experiment was conducted to assess the effect of NPK fertilizers on seedling growth and survival of five important mangrove species of Bangladesh for nine months. Seedlings were raised in the nursery using plastic pots. NPK fertilizers with three treatments (control, 4 gm and 8 gm doses) were used two times when seedlings age was 3 and 6 months. The result showed that seedlings height growth of Excoecaria agallocha was enhanced significantly with the application of NPK fertilizers but it was shown negatively significant effect on height growth of Xylocarpus mekongensis after second time fertilizer application. Moreover, NPK application enhanced mortality of Avicennia officinalis and Ceriops decandra seedlings in both times of fertilizer application. But no effect of NPK fertilizers on seedlings growth and survival of Heritiera fomes were observed.